(untitled) (Acta Scientiarum. Agronomy, 2022)
Grapevine is a fruit species of great agronomic interest since both fresh fruit and wine are highly marketable products. Therefore, there is growing interest in this crop among researchers in the pursuit of increased yields and better cultivation conditions. Asexual propagation is the most commonly used method for propagating grapevine seedlings, with cuttings used for rootstock formation and subsequent grafting of materials to form the canopy. The rootstock is responsible for support, water, and nutrient uptake, thus determining the vigor of the plant; therefore, it is essential to understand the suitable conditions in which roots can thrive and thereby enhance plant growth. The type of cutting, type of substrate, and application of exogenous auxins are among the factors that interfere with the rooting of grapevine rootstocks, and determining and implementing the best combination of these factors could provide for more vigorous plants. Reviewing high-quality published scientific research from diverse countries is a method of identifying data, grouping information, and obtaining reliable answers. Furthermore, it can allow for the detection and grouping of the main factors affecting the rooting of grapevine cuttings, thus enabling a clearer recommendation and better understanding of the issue.